Seed morphological traits and early imbibition dynamics of three local Madura sorghum accessions - Putri Andini Mandasari; Sinar Suryawati; Arifah Husna; Yuni Nurfiana (Universitas Trunojoyo Madura, 2026)
Sorghum is a cereal crop that is tolerant to dry conditions, making it potentially suitable for cultivation in drylands in Madura. This study aimed to describe seed morphological characteristics and early imbibition dynamics, and to evaluate the relationship between these two characteristics in three local Madura sorghums. The observed seed morphological characteristics included color, length, width, and thousand-seed weight, while the percentage of water absorption determined imbibition dynamics during the first 1–4 hours. The data were analyzed descriptively, followed by Pearson's correlation analysis and principal component analysis (PCA). Descriptive analysis revealed variation in seed morphological traits and early imbibition patterns among the three local Madura sorghum accessions. SPG2 showed a rapid early imbibition pattern, SPG1 exhibited a gradual increase in water uptake, whereas BKL displayed slow initial imbibition followed by a steady increase throughout the observation period. Positive correlations were observed among seed morphological traits, whereas negative correlations were found between seed morphological traits and early imbibition during the first three hours (IMB1–IMB3). PCA analysis showed that imbibition dynamics and thousand-seed weight were the traits that contributed the most to data diversity (PC1 = 71.4%). The results of this study provide basic information for characterizing local Madura sorghum germplasm.